Transcutaneous Detection of Intramural Microchips for Tracking the Migration of the Equine Large Colon: A Pilot Study - Sara KT Steward; Hannah M. McKee; Allison M. Watson; Mo D. Salman; Diana M. Hassel (Animals, 2022)
Colic remains the number one cause of mortality in horses, and large colon displacement including colonic volvulus is one of the leading causes for equine hospitalization and surgery. Currently, there is not an adequate model to study the pathophysiology of this condition. The objective of this proof-of-concept study was to determine if subserosal implantation of bioinert microchips in the large intestine would be detectable by a RFID (radio-frequency identification) receiver when the implanted microchips were adjacent to the body wall, thus identifying the location of the colon within the abdomen. A horse with no history of gastrointestinal disease underwent a ventral midline celiotomy to implant twelve bioinert microchips into the subserosa at predetermined locations within the large colon and cecum. A RFID scanner was used to monitor the location of the colon via transcutaneous identification 1–3 times daily for a one-month period. Following humane euthanasia, a postmortem examination of the horse was performed to assess microchip implantation sites for migration and histologic assessment. Eleven out of the 12 implanted microchips were successfully identified transcutaneously at occurrences as high as 100%. Odds ratios were calculated for the likelihood of identifying each chip in a location different from its most common location. Microchips implanted into the subserosa of the equine large colon can be used as a means of identifying the approximate location of the equine large colon via transcutaneous identification with an RFID scanner.